(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Globalization is the new buzzward that has come to dominate the world since the 90’s of the last century with the end of the gold war and break-up of the former soviet union & the global trend towards the rolling ball. Through globalization has generated significant international opposition over concerns that it has increased inequality and environmental degradation. There is need to study the impact of globalization on developing countries from the view point of inward foreign direct investment. Globalization has brought in new opportunities to developing countries. Greater access to developed country markets and technology transfer hold out promise improved productivity and higher living slandered.